Which Factor Influences Environmental Care Characters More: Knowledge of Issue or Demographic Factors? - Azmi Al Bahij; Nidar Yusuf; Lativa Qurrotaini; Khairadha Maharani (Profesi Pendidikan Dasar, 2021)
The background of this research was due to the lack of people’s awareness to their environment. A report by Indonesian Central Statistics Agency in 2018 stated that the Indonesian Environmental Ignorance Behavior Index (IPKLH) in 2018 is 0.72. The number indicates a high level of ignorance on waste management. That being said, the character of environmental care in society is still low. Therefore, the researcher was moved to study the influence of knowledge issues and demographic factors on environmental care for elementary school students. A quantitative survey was utilized as a research methodology. In this study, 119 people were included as a sample. Of the questionnaire instrument for the character of environmental care, the researcher had adjusted to the life of elementary school students. The questionnaire instrument was then analyzed using SPSS version 22.0 with simple regression technique and multiple regression. The result showed that the significant value obtained by all variables is 0.001 or P 0.05. That being said, Ha wa accepted, and Ho was rejected, or it displays that there was an influence between each of them. The percentage obtained respectely is 4.4%  and 9.4%